Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Dan Free Cash Flow Terhadap Manajemen Laba Riil Dengan Kepemilikan Institusional Sebagai Variabel Moderating(Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Mayesti, Miftha Adelina; , Dr. Triyono, SE., M.Si (2017)
The aim of this research was to analyzed the effect of capital structure as measured by profitability, leverage, the size of the company and free cash flowonreal earning management with institusional ownership as variable moderation in manufacturing companies listed on the Indonesia stock exchange the period 2011- 2015. The sampling method used in this research is purposive sampling with the total sample as much as 310 companies. Analysis used by multiple regression methode with Moderated Regression Analysis (MRA).. The results showed that profitability, the company's size and institusional ownership has a effect on real earnings management while the leverage andfree cash flowhave no effect on real earnings management. The size of the company,and free cash flowis moderated by institusional ownership have no effect on real earnings management. The profitability and leverage is moderated by institusional ownership has aeffect on real earnings management.